2014
DOI: 10.1007/s11999-014-3548-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Aspirate Concentrate and Platelet-rich Plasma Enhanced Bone Healing in Distraction Osteogenesis of the Tibia

Abstract: Background During lower limb lengthening, poor bone regeneration is a devastating complication. Several local or systemic applications have been used to promote osteogenesis, and biologic stimulations are gaining attention, but their utility has not been proven in this setting. Questions/purposes In patients undergoing bilateral tibial lengthening, we compared those receiving an osteotomy site injection of autologous bone marrow aspirate concentrate (BMAC) plus platelet-rich plasma (PRP) with those not receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 57 publications
0
56
0
1
Order By: Relevance
“…, by vacuum aspiration) from the iliac crest to facilitate the availability of autologous bone marrow and the establishment of a standardized dose of stromal cells and mononuclear cells in a well-prepared BMC product [560]. For many years, it has been recognized that BMC may possess high potency in cartilage and osseous defect healing when used in combination with grafting materials and occasionally PRP [561565]. However, there are no published randomized controlled trials on the efficacy of autologous BMC intra-articular injections performed as a same-day, in-office procedure for treating patients with cartilage or bone disease [566].…”
Section: Preparations Containing Non-expanded Autologous Stromal Cmentioning
confidence: 99%
“…, by vacuum aspiration) from the iliac crest to facilitate the availability of autologous bone marrow and the establishment of a standardized dose of stromal cells and mononuclear cells in a well-prepared BMC product [560]. For many years, it has been recognized that BMC may possess high potency in cartilage and osseous defect healing when used in combination with grafting materials and occasionally PRP [561565]. However, there are no published randomized controlled trials on the efficacy of autologous BMC intra-articular injections performed as a same-day, in-office procedure for treating patients with cartilage or bone disease [566].…”
Section: Preparations Containing Non-expanded Autologous Stromal Cmentioning
confidence: 99%
“…[37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Nevertheless, it takes time to apply it to cases, which makes its bioactive and effective treatment results controversy.…”
Section: -2234mentioning
confidence: 99%
“…8 However, as there are contradictory results reported in some cases in literature where PRP was applied, there are some questions regarding the efficiency of PRP treatment. [16][17][18] Some manuscripts indicated that PRPs with different contents are superior in clinical treatment. 19 There was no well-proven study in which PLT and leucocyte (WBC) rates were separately discussed in PLT concentrations in PRP content.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical importance of these findings remains questionable 121 . A randomized study revealed a 27% reduction in external fixation time with the use of low-intensity pulsed ultrasound for tibial osteoplasty 122 .…”
Section: Fractures and Poor Bone Formationmentioning
confidence: 99%